Justification of the need to supplement the list of limitations regarding the use of lands and land plots by environmental and technological limitations - Dorosh, Y.; Dorosh, O.; Stetsiuk, M.; Kharytonenko, R. (Land Management, Cadastre and Land Monitoring, 2022)
The need for improvement and adaptation of the existing norms for land protection, rational use of land plots with the legislative norms of the European Union has been identified. The work of scientists, current land legislation, other legal acts related to ecological and technological restrictions have been studied. It was established that the existing "List of restrictions on the use of land and land plots" approved by resolutions of the Cabinet of Ministers of Ukraine No. 1051 and No. 821 does not provide for a complete list of restrictions on the use of agricultural land, in particular ecological and technological restrictions. Also, the main restrictions on the use of land, provided by ecological and technological groups on arable land based on the steepness of the slopes, were considered. It was noted that the current legislative norms of the Code of Ukraine on administrative offenses in the field of nature protection and use of natural resources provide for liability for violations of land use rules. It is emphasized that in the absence of ecological and technological restrictions in the information of the State Land Cadastre, landowners and land users neglect the norms of ecological and technological restrictions in conducting economic activities on arable land, and it is established that there are no mechanisms for holding them accountable in case of their violation. Proposals are presented in addition to resolutions of the Cabinet of Ministers of Ukraine No. 1051 and No. 821 in the "List of restrictions on the use of land and land plots" with ecological and technological restrictions on arable land. Keywords: ecological-technological restrictions, ecological-technological groups, arable land, restrictions on the use of land plots, State Land Cadastre.